Hubungan obesitas sentral dengan testosterone deficiency syndrome (TDS) pada laki-laki dewasa di Denpasar tahun 2017 - Ida Ayu Gde Wahyudevi Dharmika; Made Oka Negara; Yukhi Kurniawan (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2018)
Background: Nutrition problem is a problem that often occurs in the population in the 21st century. One of the nutritional problems that often occur as a result of lifestyle is central obesity. Central obesity is a metabolic abnormality of the body accompanied by visceral fat accumulation in the abdominal area, and is an important health problem. Males are said to be central obese if abdominal circumference ≥ 90cm. In men, central obesity can lead to a decrease in testosterone levels. Testosterone Deficiency Syndrome (TDS) is a set of symptoms associated with decreased sexual satisfaction or decreased general state of feeling resulting from decreased testosterone levels in men. Method: A cross sectional analytical research conducted at Niti Mandala Renon Denpasar Field, with the number of sampelts 55 men aged 40-60 years. Sampelts filled out the Aging Males’ Symtomps (AMS) questionnaire, and also measured the abdominal circumference. Data were analyzed using SPSS program. Results: Of the 55 sampels, 41 (74.5%) were central obesity, and non-central obese were 14 (25.5%) sampels. It was found that there were 27 sampelts (29.1%) of sampelts who had TDS as many as 28 (50,9%) sampelts. From the result of chi-square test, there was significant correlation between central obesity with TDS in adult male in Denpasar (p = 0,016, RR = 5,176 (CI95% 1,252-21,411)). Conclusion: Central obese men have a risk of TDS 5.176 times faster as against who are not one.